2007
DOI: 10.1590/s1676-06032007000100031
|View full text |Cite
|
Sign up to set email alerts
|

New record of Amphisbaena fuliginosa (Squamata, Amphisbaenidae) for the Cerrado Biome, in an area of extensive cattle ranching

Abstract: Samples of Amphisbaena fuliginosa from the Cerrado biome are scarce and additional data are needed to clarify the geographic distribution and patterns of differentiation of this species. During field works at a cattle farm in the south of the state of Goiás, Central Brazil, we found an adult individual of A. fuliginosa. Our specimen represents the southernmost record for the species, extending its distribution 150 km. The color is similar to that described for other specimens from Goiás state, corroborating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Overall, roadkill events were relatively infrequent in urban areas and within the areas with intense anthropogenic impacts (quarries, wind farms). Otherwise, C. thous appears to be well adapted to modified landscapes, such as pastures, sugarcane plantations, other crops, and suburban areas (Dotta and Verdade, 2007;Lemos et al 2011). In general, the distribution of the roadkill events documented in the present study study is consistent with the pattern observed in previous studies, in particular, the ecological characteristics of the habitats most occupied by the species.…”
Section: Spatial Distribution Of the Roadkillsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, roadkill events were relatively infrequent in urban areas and within the areas with intense anthropogenic impacts (quarries, wind farms). Otherwise, C. thous appears to be well adapted to modified landscapes, such as pastures, sugarcane plantations, other crops, and suburban areas (Dotta and Verdade, 2007;Lemos et al 2011). In general, the distribution of the roadkill events documented in the present study study is consistent with the pattern observed in previous studies, in particular, the ecological characteristics of the habitats most occupied by the species.…”
Section: Spatial Distribution Of the Roadkillsupporting
confidence: 90%
“…habitats and more open vegetation (Lemos et al 2011), the roadkill hotspot may coincide with dispersal routes, which the foxes use to avoid areas of denser vegetation. This is supported by the plots (Figures 12 and 13), which show the predominant vegetation and rainfall rates of the study area.…”
Section: Roadkill Hotspotsmentioning
confidence: 99%
“…The crab-eating fox prefers edge habitats and open areas over dense forest, and is often observed in pastures and moving along the margins of highways (Dotta and Verdade, 2007;Lemos et al 2011). This is consistent with the high frequency of roadkill in areas where the vegetation is sparse or shrubby.…”
Section: Spatial Distribution Of the Roadkillsupporting
confidence: 66%
“…Overall, roadkill events were relatively infrequent in urban areas and within the areas with intense anthropogenic impacts (quarries, wind farms). Otherwise, C. thous appears to be well adapted to modi ed landscapes, such as pastures, sugarcane plantations, other crops, and suburban areas (Dotta and Verdade, 2007;Lemos et al 2011). In general, the distribution of the roadkill events documented in the present study study is consistent with the pattern observed in previous studies, in particular, the ecological characteristics of the habitats most occupied by the species.…”
Section: Spatial Distribution Of the Roadkillmentioning
confidence: 99%
See 1 more Smart Citation